2020
DOI: 10.18203/2394-6040.ijcmph20201530
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, perceived risk and protective behaviours of Myanmar adults on COVID-19

Abstract: Background: COVID-19 was originated from Wuhan city, China in December 2019 and spread very fast to all over the world. This study was carried out to assess the awareness, perceived risk and protective behaviours of Myanmar adults on COVID-19.Methods: The cross-sectional study was conducted using face to face interview method among 597 adults from Yangon and Bago regions. Binary logistic regression analysis was done to determine the factors influencing on practicing protective behaviours and the results were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
47
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 3 publications
17
47
2
1
Order By: Relevance
“…The results showed that gender, educational level, and preventive strategies are signi cant factors in the understanding of individuals. These ndings were similar to the study conducted in Myanmar adults on awareness, perceived risk, and protective behaviors to COVID-19 and in Saudi Arabia [20], [24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that gender, educational level, and preventive strategies are signi cant factors in the understanding of individuals. These ndings were similar to the study conducted in Myanmar adults on awareness, perceived risk, and protective behaviors to COVID-19 and in Saudi Arabia [20], [24].…”
Section: Discussionsupporting
confidence: 88%
“…The study found that mass media and public health care workers were the most important sources of information for Sheka Zone, Tepi Town city administration individual's awareness towards COVID-19. These ndings were similar to Myanmar adults study the familiar sources were social media and mass media [20]. Also in Hong Kong study in which their common sources were social platform and mass media but different with health care workers study in which their primary sources were not only social media but also o cial government websites [21], [22] and in Pakistan healthcare professionals study [23].…”
Section: Discussionsupporting
confidence: 67%
“…The study found that mass media and public health care workers were the most important sources of information for Sheka Zone, Tepi Town administration individual's awareness towards COVID-19. These ndings were similar to Myanmar adults study the familiar sources were social media and mass media [20].Also in Hong Kong study in which their common sources were social platform and mass media but different with health care workers study in which their primary sources were not only social media but also o cial government websites [21], [22] and in Pakistan healthcare professionals study [23].…”
Section: Discussionsupporting
confidence: 67%
“…Results from this study showed that about 6 out of every 10 of respondents had a high level of perceived risk of contracting COVID-19. This is signi cantly higher compared to ndings among Myanmar population where less than one-fourth of respondents had high level of risk perception towards COVID-19 (Mya et al, 2020). The elevated perceived risk level might be attributed to disparity in country experience.…”
Section: Discussioncontrasting
confidence: 58%